2016
DOI: 10.1017/s002966511600063x
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep duration in diabetes and glucose control

Abstract: Sleep curtailment is common in the Westernised world and coincides with an increase in the prevalence of type 2 diabetes mellitus (T2DM). This review considers the recently published evidence for whether sleep duration is involved in the development of T2DM in human subjects and whether sleep has a role to play in glucose control in people who have diabetes. Data from large, prospective studies indicate a U-shaped relationship between sleep duration and the development of T2DM. Smaller, cross-sectional studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A significant association between a short sleep duration and prediabetes is consistent with many previous studies[ 1 , 3 , 5 , 6 - 13 , 15 , 16 ]. This association could be explained by physiological mechanisms, such as insulin resistance[ 27 , 28 ], decreased leptin levels, increased ghrelin levels and inflammation, sympathetic nervous system activation, and oxidative stress[ 29 ]. This association could also be explained by behavioral mechanisms, such as increased food intake, and unfavorable lifestyles, such as smoking and sedentary behavior[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant association between a short sleep duration and prediabetes is consistent with many previous studies[ 1 , 3 , 5 , 6 - 13 , 15 , 16 ]. This association could be explained by physiological mechanisms, such as insulin resistance[ 27 , 28 ], decreased leptin levels, increased ghrelin levels and inflammation, sympathetic nervous system activation, and oxidative stress[ 29 ]. This association could also be explained by behavioral mechanisms, such as increased food intake, and unfavorable lifestyles, such as smoking and sedentary behavior[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal glucose metabolism have been linked to disturbances of different aspects of sleep, including sleep duration, quality, respiratory function during sleep, and circadian timing 41 . Both short and long sleep durations are associated with worse glucose control in people with diabetes 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a U-shape relationship between the duration of sleep and risk of T2DM ( 56 58 ), with the lowest risk among those who slept 7–8 h per night ( 59 ). Compared with 7 h of sleep, the risk for developing diabetes ranged between 1.47 and 1.95 for shorter sleep duration and between 1.4 and 3.12 for longer sleep duration ( 60 ). Other studies have shown positive association between long, but not short, sleep duration and diabetes ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%